Disposition of 4-bromo-2,5-dimethoxyphenethylamine (2C-B) and its metabolite 4-bromo-2-hydroxy-5-methoxyphenethylamine in rats after subcutaneous administration - Rohanová, Miroslava; Pálenícek, Tomás; Balíková, Marie (Toxicology letters, 2008)
The psychedelic compound 4-bromo-2,5-dimethoxyphenethylamine (2C-B) has appeared as an agent in drug abuse or overdose cases in humans. The human pharmacokinetics of this drug is unknown and only partial information is available on its metabolites. Our experimental study was focused on the disposition and kinetic profile of 2C-B in rats after subcutaneous administration using a GC-MS validated method. One of the major metabolites 4-bromo-2-hydroxy-5-methoxyphenethylamine (2H5M-BPEA) was confirmed in rat tissues of lung, brain, liver and was quantitatively evaluated as well. The disposition of 2C-B was characterized by its estimated half-life 1.1h and estimated volume of distribution 16L/kg. The lung susceptibility for drug retention and gradual temporal release parallel to the brain were ascertained. The drug penetrating the blood/brain barrier was without significant delay. 2C-B brain to serum ratio attained a maximum value of 13.9 and remained over the value of 6.5 to the end of our observation (6h after the dose). The distribution of the hydroxylated metabolite 2H5M-BPEA into the lipophilic brain tissue was less efficient in relation to the parent compound. The kinetics of the drug partitioning between blood to brain may be important for the subsequent assessment of its psychotropic or toxic effects.
Keywords: Male; Rats; 2,5-dimethoxy-4-methylamfetamin; Brain; aplikace kožní; dimethoxyfenylethylamin; Psychotropic Drugs; psychotropní léky; potkani Wistar; játra; plíce; Animals; Liver; Dimethoxyphenylethylamine; Lung; zvířata; mužské pohlaví; DOM 2,5-Dimethoxy-4-Methylamphetamine; mozek; krysa rodu Rattus; Rats, Wistar; Administration, Cutaneous